Sardaryan T. G. On the solvability of one system of nonlinear Hammerstein-type integral equations on the semiaxis - Sardaryan, T. G.; Terjyan, Ts. E.; Khachatryan, Kh. A. (Ukrains’kyi Matematychnyi Zhurnal, 2017)
We study the problems of construction of positive summable and bounded solutions for the systems of nonlinearHammerstein-type integral equations with difference kernels on the semiaxis. The indicated systems have direct applicationsto the kinetic theory of gases, the theory of radiation transfer in spectral lines, and the theory of nonlinear Ricker competitionmodels for running waves.